A POSSIBLE ANOMALOCARIDID FROM THE CAMBRIAN SIRIUS PASSET LAGERSTATTE, NORTH GREENLAND - Daley, A; Peel, J (2010)
The Sirius Passet biota of North Greenland is one of the oldest Cambrian lagerstätten, and although it is dominated by non-mineralized arthropods and lobopods, anomalocaridids have never been identified. Based on a single specimen, we herein describe for the first time an appendage with possible anomalocaridid affinities as suggested by an overall gross morphology similar to that of the frontal appendage of Anomalocaris from other localitites. Tamisiocaris borealis n. gen. and n. sp. has an elongated appendage with paired spines along one margin, and differs from the frontal appendage of Anomalocaris in that segment boundaries are absent and ventral spines are relatively long and spineless. These differences may be taphonomic, but the entire surface of the appendage is covered in a fine fabric, making it unlikely that this appendage was originally segmented or sclerotized. The taxon is tentatively placed within Radiodonta, but this systematic placement cannot be confirmed while complete body specimens are lacking. © 2010 The Paleontological Society.